2015
DOI: 10.1371/journal.pone.0120078
|View full text |Cite
|
Sign up to set email alerts
|

Standard Sub-Thermoneutral Caging Temperature Influences Radiosensitivity of Hematopoietic Stem and Progenitor Cells

Abstract: The production of new blood cells relies on a hierarchical network of hematopoietic stem and progenitor cells (HSPCs). To maintain lifelong hematopoiesis, HSPCs must be protected from ionizing radiation or other cytotoxic agents. For many years, murine models have been a valuable source of information regarding factors that either enhance or reduce the survival of HSPCs after exposure of marrow to ionizing radiation. In a recent series of studies, however, it has become clear that housing-related factors such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…Compared to the standard housing temperature (22°C), thermoneutrality (30°C) suppresses the SNS, promotes HSPC apoptosis, and increases the radiosensitivity of mice. 53 Consistent to the previous finding, 53 we did not observe any difference in BM cellularity ( Online Supplementary Figure S9A ) or the frequency of LSK, MP, and CLP (Online Supplementary Figure S9B) between mice housed at 22°C and 30°C. However, thermoneutrality increased the ratio of MEP to GMP and the ratio of CLP to CMP ( Online Supplementary Figure S9C and D ).…”
Section: Resultssupporting
confidence: 91%
“…Compared to the standard housing temperature (22°C), thermoneutrality (30°C) suppresses the SNS, promotes HSPC apoptosis, and increases the radiosensitivity of mice. 53 Consistent to the previous finding, 53 we did not observe any difference in BM cellularity ( Online Supplementary Figure S9A ) or the frequency of LSK, MP, and CLP (Online Supplementary Figure S9B) between mice housed at 22°C and 30°C. However, thermoneutrality increased the ratio of MEP to GMP and the ratio of CLP to CMP ( Online Supplementary Figure S9C and D ).…”
Section: Resultssupporting
confidence: 91%
“…The key to reproducibility is accurate reporting of these seemingly mundane details, which potentially have large effects ' [87]. Although housing temperature was not included as a factor in these analyses, studies are accumulating in which experimental outcomes differ depending on the ambient temperature; these are summarized in Figure 1 [7,10,11,19,27,28,40,42,44,46,48,63,66,67,70,79,84,[88][89][90][91][92][93][94] biomedical applications, and how this condition may influence decisions for translation to the clinic (see Outstanding Questions). It is likely that many, if not all, of the metabolic abnormalities noted previously in mouse models stem largely from chronic mild cold stress and the increase in adaptive thermogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the role for UCP1 in adaptive adrenergic thermogenesis, which had been questioned on the basis of negative results obtained in mice housed at 22˚C, was confirmed when chronic cold stress was alleviated by housing at 30˚C, clearly demonstrating the significance of considering ambient housing temperatures when planning and interpreting experiments. To our knowledge, our group first reported that mouse models of cancer and antitumor immunity (39)(40)(41), immune responses in graft versus host disease (42), dendritic cell biology (43), and radiosensitivity of hematopoietic stem cells (44) are each significantly influenced by room temperature. These are representative of a growing number of papers reporting how choice of housing temperature impacts experimental outcomes and reproducibility in several mouse models of disease and we have recently reviewed this topic (45)(46)(47).…”
Section: Housing Temperatures For Mice Affect Chronic Adrenergic Strementioning
confidence: 99%